Gas-Liquid Mass Transfer in an Unbaffled Vessel Agitated by Unsteadily Forward-Reverse Rotating Multiple Impellers - Yoshida, Masanori; Yamagiwa, Kazuaki; Ohkawa, Akira; Tezura, Shuichi (IntechOpen, 2011)
None